TESTIMONY OF THE CONSTRUCTION MASTER WHO HAVE NO COMPETENCE IN THE CASE OF CORRUPTION - Sera Rosanto (Jurnal Pembaharuan Hukum, 2018)
Calculation of state losses can only be done by a master . Master  here are not only master  in the field of financial audit but also engineers who will calculate the feasibility of construction of a building in case of corruption was related to the construction field. Master  who has the competence docalculating the quantity of a building and the price of a building is a person who has a construction management certification. Description of the Construction Master  who have no competence in the matter of corruption, the statement becomes invalid.